1998
DOI: 10.1161/01.cir.97.19.1960
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-Receptor Tyrosine Kinase Blocker AG1295 Selectively Attenuates Smooth Muscle Cell Growth In Vitro and Reduces Neointimal Formation After Balloon Angioplasty in Swine

Abstract: The tyrphostin AG1295, a selective blocker of PDGF-receptor kinase, exerts a marked inhibitory effect on the activation, migration, and proliferation of porcine and human SMCs in vitro and an approximately 50% inhibitory effect on neointimal formation after balloon injury in porcine femoral arteries when delivered via biodegradable nanoparticles. Further studies appear to be warranted to evaluate the applicability of this novel approach to the interventional setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(106 citation statements)
references
References 31 publications
2
104
0
Order By: Relevance
“…[31][32][33] Banai and co-workers reported that in vivo delivery of the PDGF-R-specific tyrphostin AG1295 caused a significant reduction (Ͼ80%) in the numbers of smooth muscle cells in the intima/media area of porcine femoral arteries after balloon injury. 31 Other investigators reported that administration of the PDGF-R-specific 2-phenylaminopyrimidine, CGP53716, inhibited an increase in intimal vascular smooth muscle cell number after balloon injury in rats by inhibiting both the migration and proliferation of smooth muscle cells. 33 At least one other blocking strategy that does not involve targeting tyrosine kinases has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Banai and co-workers reported that in vivo delivery of the PDGF-R-specific tyrphostin AG1295 caused a significant reduction (Ͼ80%) in the numbers of smooth muscle cells in the intima/media area of porcine femoral arteries after balloon injury. 31 Other investigators reported that administration of the PDGF-R-specific 2-phenylaminopyrimidine, CGP53716, inhibited an increase in intimal vascular smooth muscle cell number after balloon injury in rats by inhibiting both the migration and proliferation of smooth muscle cells. 33 At least one other blocking strategy that does not involve targeting tyrosine kinases has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Each treatment was performed in triplicate with the cells being treated continuously for 9 days. The concentrations of angiogenic inhibitors used were based on IC 50 values and previously reported concentrations (Banai et al 1998, Kurimoto et al 2004, Hatziapostolou et al 2006, Sugiura et al 2007, Wang et al 2007. A further experiment was carried out to investigate the production of progesterone (nZ6 additional cultures).…”
Section: Effect Of Angiogenic Inhibitors On Endothelial Cell Network mentioning
confidence: 99%
“…With their low molecular weight and hydrophobic characteristics, tyrphostins can more easily gain access to receptor sites deep within tissues such as the arterial media (162). In vitro experiments have shown that the tyrphostin AGL-2043, as well as the related tyrphostin AG-1295, selectively inhibit PDGF receptors and selectively inhibit SMC proliferation in culture (163). Local delivery of AG-1295 by a perivascular polymeric matrix or intraluminally with nanoparticules inhibited intimal hyperplasia in a rat carotid injury model (164,165).…”
Section: Perlecanmentioning
confidence: 99%